1997
DOI: 10.14430/arctic1113
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Predictions of Arctic Climatic Change: Potential Effects on Marine Mammals

Abstract: ABSTRACT. Recent analyses have revealed trends over the past 20-30 years of decreasing sea ice extent in the Arctic Ocean coincident with warming trends. Such trends may be indicative of the polar amplification of warming predicted for the next several decades in response to increasing atmospheric CO 2 . We have summarized these predictions and nonuniform patterns of arctic climate change in order to address their potential effects on marine mammals. Since recent trends in sea ice extent are nonuniform, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
186
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(194 citation statements)
references
References 79 publications
4
186
0
1
Order By: Relevance
“…The most significant threats to arctic marine mammals comprise loss of sea ice habitat and its associated highly productive food web along with the increase in anthropogenic activities at high latitudes (Ragen et al 2008). The effects of declining sea ice on marine mammals are likely to be reflected in the shifting of marine mammal populations (or smaller units) to higher latitudes by either direct movement and/or indirect shifts associated with increased mortality and decreased reproduction at lower latitudes, coincident with decreased mortality and increased reproduction at higher latitudes (Tynan and DeMaster 1997). The overall combined effects of environmental perturbations caused by climate change could ultimately result in the displacement of some populations from their current geographical ranges and ultimately in the extinction of some marine mammal species (Kovacs et al 2010).…”
Section: Climate Change and The Diet Of Bowhead Whalesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant threats to arctic marine mammals comprise loss of sea ice habitat and its associated highly productive food web along with the increase in anthropogenic activities at high latitudes (Ragen et al 2008). The effects of declining sea ice on marine mammals are likely to be reflected in the shifting of marine mammal populations (or smaller units) to higher latitudes by either direct movement and/or indirect shifts associated with increased mortality and decreased reproduction at lower latitudes, coincident with decreased mortality and increased reproduction at higher latitudes (Tynan and DeMaster 1997). The overall combined effects of environmental perturbations caused by climate change could ultimately result in the displacement of some populations from their current geographical ranges and ultimately in the extinction of some marine mammal species (Kovacs et al 2010).…”
Section: Climate Change and The Diet Of Bowhead Whalesmentioning
confidence: 99%
“…1). Spectacular examples of these hyper-specialists endemic to arctic seas are the polar bear, the walrus and the narwhal, all of which depend on sea ice for hunting, reproduction and/or protection (Stirling 1997;Tynan and DeMaster 1997). These predators and several other large vertebrate carnivores, including fish and birds, in turn rely on the energy transferred from the microalgal primary producers by the lower trophic levels of the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…Significant reduction in ice edge extent could have deleterious effects on marine mammals that depend upon these systems (Tynan and DeMaster 1997). Walrus are vulnerable to changes in sea ice extent, as floating ice provides them with a means of transportation and allows them to feed over large areas (Alexander 1994).…”
Section: Ocean Margin Ecosystems and Fishery Resourcesmentioning
confidence: 99%
“…Walrus are vulnerable to changes in sea ice extent, as floating ice provides them with a means of transportation and allows them to feed over large areas (Alexander 1994). Ringed seals depend upon the stability of fast ice for raising their young; they and the polar bears which prey upon them are the only marine mammals that regularly occupy landfast Arctic ice (Stirling 1997;Tynan and DeMaster 1997) and would presumably be greatly affected by a reduction of the extent of sea ice. Anecdotal evidence suggests that the availability of walrus, polar bears, and other marine mammals to native hunters in the Arctic has already been declining (Weller and Anderson 1998).…”
Section: Ocean Margin Ecosystems and Fishery Resourcesmentioning
confidence: 99%
“…The observed differences in mother-pup behavior could therefore be related to geographic differences in environmental conditions. Recent climatic variations have resulted in changes in the dynamics of ice and thaw, increasing the unpredictability of ice cover in all Arctic areas (Tynan & DeMaster 1997, Serreze et al 2003. Serreze et al (2003) reported a record minimum Arctic sea ice extent in 2002, the year during which the behavioral and acoustic data were collected in the Greenland Sea.…”
Section: Mother-pup Behaviormentioning
confidence: 99%